REINFORCEMENT OF REINFORCED CONCRETE AND BRICK STRUCTURES WITH COMPOSITE MATERIALS - Davlyatov Shohrukh Muratovich; Mamadaliyev Mirzaahmad Muzaffarjon ogli (Journals Park Publishing, 2022)
The article provides information about the properties of composite reinforcement, its main advantages and disadvantages compared to traditional steel reinforcement. The areas of application of composite reinforcement are considered, examples are given in which it is advisable to use this type of reinforcement.
Keywords: reinforcement, fiberglass, fiberglass, composite reinforcement, steel reinforcement, concrete